THE INFLUENCE OF INTERNATIONAL COMPETITION ON THE STRATEGIC DEVELOPMENT OF THE COUNTRY’S ECONOMY - MYKYTYN, Oleh (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The study draws attention to the problems and prospects of sustainable strategic development of the national economy. That is why the purpose of the article is the further development of methodological and applied principles and approaches to analyzing the impact of international competition on the strategic development of the country’s economy. Scientific views on the interpretation of international competition are summarized, in particular, according to the geopolitical, economic, resource, political and institutional approach. The main factors of the influence of international competition on the strategic development of the national economy have been determined, namely in terms of the possible rapid accumulation of economic resources by the country, the availability of information about prospective and current needs of potential buyers, ensuring the country’s competitiveness on the international market, the favorability of the national system of economic support and the development of factor competitive advantages. The trends of international competition and expected changes in the strategic development of the country’s economy have been identified and characterized, in particular in terms of such components as the technologicalization of the world economy, the blurring of global industry boundaries, the globalization of international competitive relations, the polarization of world market segments, the deregulation of world market segments. The most significant manifestations of international competition have been identified, which relate to the global nature of international competition, its multifacetedness, dynamism and aggressiveness of competitive rivalry, which leads to violations in stability and balance in the economies of competing countries. The directions of the strategic development of the national economy are determined, depending on the influence of factors of international competition on it.